1998
DOI: 10.1104/pp.116.2.785
|View full text |Cite
|
Sign up to set email alerts
|

Guard Cells Possess a Calcium-Dependent Protein Kinase That Phosphorylates the KAT1 Potassium Channel1

Abstract: Increasing evidence suggests that changes in cytosolic Ca2+ levels and phosphorylation play important roles in the regulation of stomatal aperture and as ion transporters of guard cells. However, protein kinases responsible for Ca2+ signaling in guard cells remain to be identified. Using biochemical approaches, we have identified a Ca2+-dependent protein kinase with a calmodulin-like domain (CDPK) in guard cell protoplasts of Vicia faba. Both autophosphorylation and catalytic activity of CDPK are Ca2+dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
2
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(104 citation statements)
references
References 66 publications
5
92
2
5
Order By: Relevance
“…Gating of anion channels in tobacco cells could be modulated by phosphorylation (Zimmermann et al, 1994). A Ca 2ϩ -dependent protein kinase may be involved in the pathway of the activation of Cl Ϫ channel (Pei et al, 1996) or K ϩ channel (Li et al, 1998). Pei et al (1997) found that abscisic acid-induced activation of anion channel is under the control of K-252a-sensitive protein kinases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gating of anion channels in tobacco cells could be modulated by phosphorylation (Zimmermann et al, 1994). A Ca 2ϩ -dependent protein kinase may be involved in the pathway of the activation of Cl Ϫ channel (Pei et al, 1996) or K ϩ channel (Li et al, 1998). Pei et al (1997) found that abscisic acid-induced activation of anion channel is under the control of K-252a-sensitive protein kinases.…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen-activated protein (MAP) kinase cascade is one of the major pathways for transmitting signals such as wounding (Usami et al, 1995;Mizoguchi et al, 1996), pathogen elicitors (Suzuki and Shinshi, 1995), drought stress (Mizoguchi et al, 1996), and hormone signaling (Seo et al, 1999). Recent studies have shown that protein phosphorylation may play a significant role in the regulation of ion channels in guard cells (Pei et al, 1996;Pei et al, 1997;Li et al, 1998). Activation of ion channels induces simultaneous efflux of K ϩ and anions, resulting in the stomatal closure due to loss of turgor in guard cells.…”
mentioning
confidence: 99%
“…More recently, a guard cell CPK has been characterized that can phosphorylate the KAT1 potassium channel and thus is likely to participate in Ca 2ϩ -regulated modulation of stomatal responses to environmental stimuli (Li et al, 1998). To further investigate the roles of CPKs involved in signaling gene expression changes leading to the induction of CAM or other stress adaptive processes, we have recently characterized a salinity-and drought-inducible CPK from common ice plant (Taybi and Cushman, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical evidence for the role of kinases in K + channel regulation was revealed by phosphorylation of KAT1 by a calcium-dependent protein kinase (CDPK) in V. faba guard cells [56]. The behavior of heterologously expressed AKT2 channels is modulated by phosphorylation, as activators of PKA type kinases abolish inward rectification [30].…”
Section: K + Channels: Properties and Regulationmentioning
confidence: 99%